Chrysanthemum indicum Flavonoid Extract on the Oxidative Stress Resistance of Caenorhabditis elegans - Hailin CUI; Hailun TANG; Lian LIU; Zuohao LI; Jingjing XIANG; Rong LI (Shipin gongye ke-ji)
To investigate the in vivo antioxidant activity of flavonoid extract from Chrysanthemum indicum and its effects on oxidative stress resistance, this study evaluated the effects of Chrysanthemum indicum flavonoid extract on the antioxidant enzyme activities and the mean lifespan of Caenorhabditis elegans (C. elegans) under oxidative stress. Moreover, the mechanisms of enhancing oxidative stress resistance in nematodes were explored by utilizing a variety of transgenic strains. The results showed that pretreatment with Chrysanthemum indicum flavonoid extract significantly prolonged the mean lifespan of worms under oxidative stress by 14.00%, 27.15%, and 18.65% (P<0.01) at concentrations of 50, 200, and 300 μg/mL, respectively. In addition, Chrysanthemum indicum flavonoid extract significantly increased the SOD activity and GSH level of C. elegans (P<0.01). Furthermore, the nuclear proportion of SKN-1 was increased from 17.16% to 51.46% in LD1 strains when treated with 200 μg/mL Chrysanthemum indicum flavonoid extract. Additionally, the results of lifespan assay of EU1 strains indicated that the lifespan extension effect of Chrysanthemum indicum flavonoid extract under oxidative stress was relied on skn-1. The mechanism of enhancing oxidative stress resistance of Chrysanthemum indicum flavonoid extract might occur by activating the transcription factor SKN-1, which in turn increased the expression of antioxidant-related proteins SOD-3, GCS-1 and GST-4. This study provides a scientific basis for the application of Chrysanthemum indicum flavonoids in alleviating oxidative stress damage.